Histamine can be Formed and Degraded in the Human and Mouse Heart - Neumann, Joachim; Grobe, Juliane M.; Weisgut, Jacqueline; Schwelberger, Hubert G.; Fogel, Wieslawa Agnieszka; Marušáková, Margaréta; Wache, Hartmut; Bähre, Heike; Buchwalow, Igor B.; Dhein, Stefan; Hofmann, Britt; Kirchhefer, Uwe; et al. (Frontiers in Pharmacology, 2021)
Histamine is metabolized by several enzymes in vitro and in vivo. The relevance of this metabolism in the mammalian heart in vivo is unclear. However, histamine can exert positive inotropic effects (PIE) and positive chronotropic effects (PCE) in humans via H2-histamine receptors. In transgenic mice (H2-TG) that overexpress the human H2 receptor in cardiomyocytes but not in wild-type littermate mice (WT), histamine induced PIE and PCE in isolated left or right atrial preparations. These H2-TG were used to investigate the putative relevance of histamine degrading enzymes in the mammalian heart. Histidine, the precursor of histamine, increased force of contraction (FOC) in human atrial preparations. Moreover, histamine increased the phosphorylation state of phospholamban in human atrium. Here, we could detect histidine decarboxylase (HDC) and histamine itself in cardiomyocytes of mouse hearts. Moreover, our data indicate that histamine is subject to degradation in the mammalian heart. Inhibition of the histamine metabolizing enzymes diamine oxidase (DAO) and monoamine oxidase (MAO) shifted the concentration response curves for the PIE in H2-TG atria to the left. Moreover, activity of histamine metabolizing enzymes was present in mouse cardiac samples as well as in human atrial samples. Thus, drugs used for other indication (e.g. antidepressants) can alter histamine levels in the heart. Our results deepen our understanding of the physiological role of histamine in the mouse and human heart. Our findings might be clinically relevant because we show enzyme targets for drugs to modify the beating rate and force of the human heart.